A psicanálise e a arte: a construção de ofícios terapêuticos em saúde mental - Domingues, Margarete Aparecida (2009)
This study aimed to analyze the speeches of mental health professionals and users on artistic doing" , considering the current reality of the work in Therapeutic Workshops in Centers of Psychosocial Attention in Mental Health Services in the State of Minas Gerais, strategies which originated from the Psychiatric Reform in Brazil. To do so, the concept of repetition according Freud, Lacan, Kierkegaard and Deleuze, emphasizing two different levels, space and time, as repetition marks difference and time. In this study, it was sought to: analyze the phenomenon described in psychoanalysis by repetition automatism starting from the speech of the actors involved in the workshops; investigate the professionals understanding of the role of art in therapy of psychotic patients; produce an articulation between the clinic of the subject that come from the psychoanalytical practice and the psychosocial clinic, and the possible reflexes of that production of subjectivity in the creation of social relationships. The psychoanalytical method was used to perform interviews and analyze findings. Semi-structured interviews were undertaken with 11 professionals and 19 users in four cities of the State, averaging 40 minutes each. In the analysis of the interviews, the analyzers who repeated more stood out as to articulate them with the phenomenon of the repetition and with the syntheses of the time extolled by Deleuze. In conclusion, therapeutic workshops, in their repetitive dimension, contributes to the rescuing of place of the subject in which he/she, user or professional, can become a artist constructer of his/her own life, because repetition brings the dimension of difference, of creation, of the possibility of new and of transgression. Therapeutic workshops, that develop the artistic activity in the perspective of creation, of new, of becoming, through the production of events, experiences, actions and objects, make it possible for man to reinvent the world in which he lives. Therefore, turning the workshop into a place of potency allows the protagonists of that scene to become inventive and creative. It is fundamental that the workshop coordinator is aware of his/her role and the level of necessary implication to interrogate the subject and to involve him/her in his/her condition of being responsible for his/her actions and to build new social relationships. Thus, it is necessary for the professional to bet on the mentally health impaired as a subject who has not had recognition for years. When being recognized, he/she can integrate the net of the culture and search for vitality to continue his/her life always marked by a fine limit.